Polni nabori resničnostnih funkcij in Postova mreža - Vukšić, Lara (Obzornik za matematiko in fiziko, 2017)
Boolean functions are maps from ?$\{0, 1\}^n$? to ?$\{0, 1\}$? for some natural number ?$n$?. ?$P_2$? is the set of all such functions. Together with the five Maltsev operations on Boolean functions, ?$P_2$? forms a structure called function algebra. The subsets of ?$P_2$? that are closed under Maltsev operations are called the subclasses of ?$P_2$?. A set of Boolean functions is functionally complete if and only if it is not contained in any of the five ?$P_2$?'s maximal subclasses.
Keywords: funkcijska algebra; maksimalni podrazredi; Postov izrek; resničnostne funkcije